(untitled) (Zien Journal of Social Sciences and Humanities, 2023)
This article explores the important topic of the development of verbal communication in the process of personality formation. Verbal communication, being a key element of the human community, has a profound impact on the evolution of the individual. The paper examines various aspects of this interaction, including the role of language in the formation and expression of personality traits, the development of communication skills, the influence of cultural and social contexts on verbal interaction, and much more. The author analyzes modern research, conducts a synthesis of data and presents a deep review of existing concepts and theories related to the development of verbal communication in the context of personality formation. As a result of the work, practical recommendations are offered for educational and social programs aimed at supporting and improving verbal communication in the process of personality formation, as well as directions for future research in this area. This article provides a valuable contribution to understanding the importance of verbal communication for the development of the individual and society as a whole.